Persuasive Methods in News Programmes "Sharqiya Channel Harvest Program Model" - Jafat, Dr.Hameed Shaheed (Thi Qar Arts Journal, 2024)
The study aimed to identify the rational and emotional persuasive techniques used in the Al-Hasad program on Al-Sharqiya Channel. To achieve its objectives and answer its questions, the study relied on the descriptive-analytical method through content analysis of a sample consisting of 10 episodes of the Al-Hasad news program on Al-Sharqiya Channel. The study found that the rational persuasive techniques in the Al-Hasad program on Al-Sharqiya Channel were based on facts and real data, followed by the use of numbers and statistics. The emotional persuasive techniques mainly involved the use of collective common concepts, reinforcing viewpoints, and presenting them as correct. It was found that the channel did not use any techniques involving the use of specific or general slogans or preferential linguistic terms in its program. The study recommended expanding research into fear appeals that may be included in political programs and news bulletins and studying the determinants of persuasive appeals in television programs according to the demographic variables of the audience to reach a clearer theoretical framework in understanding these appeals.